The Impact of Various Concentration of Maizena Flour on the Physicochemistry and Organoleptic Properties of Petis - Sri Haryati; Sudjatinah Sudjatinah; Soraya Kusuma Putri; Paramita Apriliani (Journal of Applied Food Technology, 2021)
Shrimp is a fishery product that has a specific aroma and has a high nutritional value. Petis derived from the body fluids of fish or shrimp through a prolonged boiling process so that it becomes denser like pasta. This study aims to determine the influence of cornstarch concentration as a binder and filler material for physical, chemical and organoleptic characteristics of shrimp petis. A Completely Randomised Design was used, with 1 factor, namely the concentration of maizena flour with 5 treatments, namely P0 (100 g shrimp broth and 0 g maizena flour); P1 (100 g shrimp broth and 2 g maizena flour); P2 (100 g shrimp broth and 4 g maizena flour); P3 (100 g of shrimp broth and 6 g of maizena flour); P4 (100 g shrimp broth and 8 g maizena flour) and 4 replications. The results showed that the treatment had an effect (p <0.05) on all observation variables i.e., chemical properties (water content, ash content, protein content), physical properties (viscosity), and organoleptic properties (taste, color, aroma, and texture). The P3 treatment was chosen as the best treatment because it approached the quality requirements of shrimp paste according to SNI (Indonesian National Standard) with characteristics of water content 48.29%, ash content 1.10%, protein content 20.95%, viscosity 91.01 Cp, and taste organoleptic 4.50 (rather savory), color 4.10 (dark), aroma 1.85 (rather fishy), and texture 4.05 (thick).